PENGEMBANGAN MEDIA PEMBELAJARAN DENGAN MENGGUNAKAN ADOBE FLASH UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN IPA KELAS V SD N 050660 KWALA BINGAI - Gihari Eko Prasetyo; Ajad Sudrajat; E. Elvis Napitupulu (JURNAL TEMATIK, 2018)
This study aims to produce learning media using Adobe Flash on science subjects in class V 050660 Public Elementary School Kwala Bingai that meet the criteria of valid, practical and effective. This research refers to the 4-D model. The findings of the research are: 1) learning devices produced, in the form of: CD-shaped Learning Media has met the criteria for good / valid; 2) the effectiveness of learning devices is concluded based on the post-test results of students in the first trial the percentage of classical completeness was 86% with 30 students or 88% declared complete. And 4 students or 12% were declared incomplete. 3) Practicality of learning media for students is concluded based on teacher responses and student responses; (i) student responses to learning media in the first trial amounting to 82.36% of students stated that the media was practical, (ii) response (ii) teacher response to learning media in the first trial reached 91.67% included in the very practical category. Assessment of student learning outcomes based on the pretest and posttest was analyzed using N-Gain obtained by the average value of gain of 0.7 where in the high category.